KINEMATICS OF THE MILKY WAY FROM VELOCITIES OF YOUNG RED CLUMP GIANTS USING THE PMA AND GAIA DR2 DATA - Velichko, A. B.; Fedorov, P. N. (Одеські астрономічні публікації, 2018)
Subsample of 19,600 young red clumpgiants with distances up to 1200 pc was selected from 7.2 mln Gaia DR2 data with radial velocities using the MG vs. G − KS diagram. Ages of these stars do not exceed 2 bln years. For this stellar subsample kinematic parameters of the Ogorodnikov-Milne model as well as the Kxy-term, Solar apex coordinates L⊙, B⊙ were derived from the 3D and 2D Gaia DR2 data as well as from the PMA proper motions. It was found that values of the OMM parameters derived from the 3D and 2D Gaia DR2 data are diﬀerent. Removing stars with heliocentric distances 0-500 pc make the results consistent. For the 500-1200 pc stellar subsample value of the rotation velocity of the Galaxy at the Solar distance Vrot derived from the PMA proper motions is 205.2 ± 0.5 km s−1 while the values derived from the Gaia DR2 data are noticeably higher: Vrot(2D Gaia DR2) =217.8 ± 0.3 km s−1 and Vrot(2D Gaia DR2) =218.6 ± 0.3 km s−1 . The Kxy-term is negative and equal to −0.80 ± 0.03mas yr−1 when using 3D Gaia DR2 data while it diminishes signiﬁcantly in case of usage of Gaia DR2 and PMA proper motions.